2020
DOI: 10.1108/ijoa-02-2019-1674
|View full text |Cite
|
Sign up to set email alerts
|

In the family way: an exploration of family business resilience

Abstract: Purpose This paper aims to explore the concept of resilience set within a family business context and considers how familiness and the nature of noneconomic factors, such as relationship dynamics influence performance. This paper provides new insights into the nature and impact of familiness as a mediating device, uncovering the potential for reframing resilience theory and practice. Design/methodology/approach The paper draws on a review of the extant literature in the areas of resilience and familiness as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 136 publications
(237 reference statements)
0
39
0
Order By: Relevance
“…Runyan [39] studied how SMEs react to management crises caused by crises/natural disasters and concluded that they suffer a highly negative impact, given their vulnerability, dependence on public support, and the psychological and financial effects on their owners. This means that business owners have to be resilient to face the consequences of crises [26], as this organizational capacity will let firms remain sustainable in turbulent environments [12]. However, the level of that capacity depends on intangible factors in business owners and firms (e.g., culture, leadership), as argued by Ates and Bititci [38].…”
Section: Consequences For Sme Business and Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…Runyan [39] studied how SMEs react to management crises caused by crises/natural disasters and concluded that they suffer a highly negative impact, given their vulnerability, dependence on public support, and the psychological and financial effects on their owners. This means that business owners have to be resilient to face the consequences of crises [26], as this organizational capacity will let firms remain sustainable in turbulent environments [12]. However, the level of that capacity depends on intangible factors in business owners and firms (e.g., culture, leadership), as argued by Ates and Bititci [38].…”
Section: Consequences For Sme Business and Managementmentioning
confidence: 99%
“…However, the level of that capacity depends on intangible factors in business owners and firms (e.g., culture, leadership), as argued by Ates and Bititci [38]. Individual resilience must be joined to organizational resilience to transform and adapt the tangible, human, and intangible resources associated with new strategies [12], i.e., strategic agility as suggested by Liu et al [30], to achieve a new dynamic capacity that stimulates such behavior [12].…”
Section: Consequences For Sme Business and Managementmentioning
confidence: 99%
See 3 more Smart Citations